Evaluation of Methanolic Extract of Centella asiatica Leaves against Trypanosoma evansi - Shaba, P.; Pandey, N. N.; Sharma, O. P.; Rao, J. R.; Singh, R. K.; Mishra, A. K. (International Journal of Bio-resource and Stress Management, 2023)
This is in vitro ethno veterinary medicine screening of Centella asiatica leaves dissolved in methanolic solvent at concentrations (250-1000 μg ml-1). The methanolic plant extract (MPE) obtained was tested against Trypanosoma evansi for trypanocidal activity. It was done on Vero cells grown in Dulbecco’s Modified Eagle Medium (DMEM) and supplemented with foetal calf serum (FCS) 20-40% at appropriate conditions. In vitro cytotoxicity test of C. asiatica extract at concentrations (1.56-100 μg ml-1) was done on Vero cells but without FCS. Mice were administered with C. asiatica leaves dissolved in either water or vegetable oil at concentration (2000 mg kg-1 body weight) to determine its acute toxicity test. In vitro trypanocidal activity varied from immobilization, reduction and to the killing of trypanosomes. At 250 μg ml-1 of MPE, there was drastic reduction of average mean trypanosomes count as observed. At 750 μg ml-1 of the test extract, there was complete killing of trypanosomes at 9 h of incubation. Parasites counts decreased in concentration and time-dependent manner with significant difference (p<0.05). Both MPE of C. asiatica and diminazine aceturate, standard drug, were cytotoxic to Vero cells except at concentrations of 1.56 and 1.56-6. 25 μg ml-1. Groups of mice that were subjected to acute toxicity test survived without exhibiting acute toxic effect.